Repairing Eden : humility, mysticism, and the existential problem of religious diversity - McLeod-Harrison, Mark S., 1956- (McGill-Queen's University Press, 2005)
How do Christians keep from losing their faith when they discover that other faiths are as justified as their own? Mark McLeod-Harrison draws on his training in analytic philosophy and his knowledge of Christian mysticism to provide a compelling analysis of, and unique solution to, the problem religious diversity poses for Christians. In Repairing Eden, McLeod-Harrison describes this dilemma as an existential problem internal to the Christian faith. He suggests that Christian humility and Christian mysticism can provide a joint path toward a kind of metaphysical certainty - the mystic path, the path of bearing one's own cross - that can become a means of more deeply knowing God. Repairing Eden weaves theology, philosophy, and pastoral concerns into a spiritual-philosophical solution to a deeply important challenge to Christian faith.